Investigation of Qawā’id Al-‘Arabiyyah Learning in IIK Program Based on Ṭarīqah An-Nuṣūṣ Al-Mutakāmilah At MAN 1 Sumedang - Fayidla Nurul Fikri; Mia Nurmala; Maman Abdurahman; Syukran Syukran (Universitas Cokroaminoto Palopo, 2025)
The purpose of this study is to describe various information regarding the implementation of ṭarīqah an-nuṣūṣ al-mutakāmilah in qawā'id al-‘arabiyyah learning. This research paradigm is interpretive with a qualitative approach. The research method used is a case study. The data collection techniques used are observation, interview, and document analysis. The data analysis technique in this research uses pattern-matching theory. The results showed that ṭarīqah an-nuṣūṣ al-mutakāmilah is an applicative and interactive learning method based on Arabic texts used to improve the ability of qawā'id al- 'arabiyyah to students. This method can help students apply the material quickly. Teachers and students are actively involved in learning and use supporting books published by the Ministry of Religious Affairs of the Republic of Indonesia in 2020.